Role of Peritubular Capillaries and Vascular Endothelial Growth Factor in Chronic Allograft Nephropathy - Andrade, Luís Gustavo Modelli de [UNESP]; Viero, Rosa Marlene [UNESP]; Carvalho, M. F. C. (Elsevier B.V., 2009)
Objective. To investigate the role of peritubular capillary damage and vascular endothelial growth factor (VEGF) in chronic allograft injury and to evaluate their correlation with clinical factors.Patients and Methods. The study included 56 patients who underwent transplantation between 1987 and 2004 and experienced chronic graft dysfunction. CD34 (peritubular capillaries) and VEGF were evaluated at histologic analysis. Patients were classified into 3 groups: 47 with chronic allograft injury, 9 with pure cyclosporine toxicity, and 26 who served as the control group (time 0 biopsy).Results. Compared with the control group, CD34 total expression in chronic nephropathy was indirectly proportional to Banff stage (P < .05), and VEGF was increased in chronic allograft injury grade I or 11 or nephrotoxicity (P < .05). CD34 expression was correlated with age (P < .007) and number of acute rejection episodes (P = .005). A negative correlation was observed between expression of CD34 and of VEGF (P < .001). Low expression of CD34 was associated with risk of graft loss of 1.45 (95% confidence interval, 1.15-7.24; P = .04).Conclusion. Peritubular capillaries decreased progressively with development of chronic allograft injury. The VEGF demonstrated a bimodal behavior, increasing at the onset of nephropathy and decreasing in the final stages. Loss of peritubular capillaries was associated with worse graft survival and overexpression of VEGF.